A Critical Analysis of Islamic Law and Human Rights in Early Childhood Protection - Pascadinianti, Meidana (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
The phenomenon of human rights violations in Indonesia, such as freedom of expression, rights of minority groups, and violence against women, creates tension between Islamic law and international standards. Although Islamic law teaches the protection of the right to life and social welfare, challenges arise in its implementation in modern society. To create balance, open dialogue and a more inclusive adaptation of Islamic law are needed so that human rights are respected without ignoring Islamic values. The research method is qualitative, with a literature review. As a result, the relationship between Islamic law and human rights, especially in the context of early childhood protection, is complex but not necessarily irreconcilable. While both systems share common goals in promoting the well-being and safety of children, significant tensions arise around issues such as child labor and early marriage, where traditional interpretations of Islamic law may conflict with modern human rights standards like those in the CRC. However, through ongoing dialogue, reinterpretation of Islamic principles in light of contemporary human rights, and legal reform, it is possible to create a legal framework that respects both Islamic values and the universal rights of children. By doing so, societies can ensure that children are protected, nurtured, and allowed to grow in a safe and supportive environment, fulfilling both religious and human rights obligations.